PS 05-84 ARTERIAL RESERVOIR CHARACTERISTICS AND BLOOD PRESSURE FROM THE CENTRAL AORTA TO THE PERIPHERAL LARGE ARTERIES. (September 2016) - Peng, Xiaoqing; Schultz, Martin; Davies, Justin; Picone, Dean; Black, Andrew; Dwyer, Nathan; Roberts-Thomson, Phil; Sharman, James
Abstract : Objective: Arterial reservoir characteristics are related to blood pressure (BP) and independently predict cardiovascular events. However, it is unknown if arterial reservoir characteristics undergo modification from the central to peripheral large arteries, nor if there is a consequent influence on blood pressure (BP). We aimed to determine arterial reservoir characteristics from the aorta to the peripheral large arteries, and the associations of arterial reservoir characteristics with BP. Design and Method: Arterial reservoir characteristics (reservoir pressure; RP and excess pressure; XSP) and BP were derived from intra-arterial pressure waveforms among 53 participants (aged 62 ± 11 years, 72% male) undergoing clinically indicated cardiac angiography. Pressure waveform recordings were made via catheter pull-back in the ascending aorta, brachial (mid-humerus) and radial (wrist) arteries. Results: As per the example figure, there was a non-significant decrease in integral and peak RP from the aorta (2226 ± 990 Pa.s -1, 44 ± 18 mmHg) to brachial (2004 ± 915 Pa.s -1, 40 ± 17 mmHg) and radial arteries (1912 ± 891 Pa.s -1, 41 ± 18 mmHg) (p = 0.21 and p = 0.50, respectively). Conversely, XSP integral significantly increased from the aorta (543 ± 316 Pa.s -1 ) to brachial (857 ± 388 Pa.s -1 ) and radial arteries (957 ± 473 Pa.s -1 ) (p < 0.001). SBP increased significantly from the aorta to the brachial, and radial arteries (126 ± 20; 136 ± 19; 142 ± 21 mmHg, p < 0.001). At the aorta, there was a strong correlation between SBP and peak RP (r = 0.787; p < 0.001), and a significant weaker (z = 5.40; p < 0.001) correlation between SBP and peak XSP (r = 0.291; p < 0.001). However, these associations reversed at the radial artery, where there was a significantly stronger relationship (z = 3.29; p < 0.05) of SBP with peak XSP (r = 0.711) than with peak RP (r = 0.400). Conclusions: Arterial reservoir characteristics are modified from central to peripheral arteries, with RP remaining relatively constant, with XSP increasing significantly and being highly related to peripheral SBP. These data provide new understanding on arterial reservoir characteristics and BP physiology within the large arteries.